Problematyka przejścia wierzytelności o naprawienie szkody wyrządzonej przestępstwem — wybrane zagadnienia - Muszyńska, Anna; Jura, Angelika (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The article is devoted to the issue of the victim’s handing over a claim for compensation for damage caused by a crime to a third party by way of conclusion of a civil law contract. Reference has been made to a status of a buyer of a claim for damages, the possibility of its occurrence as a party to a criminal process, status of an aggrieved party, as well as the characteristic context of the criminal law obligation to repair a damage, with its main concepts: damage and the aggrieved party.
Keywords: przestępstwo; ofiara; szkoda; odszkodowanie; roszczenie